Komposisi Arang Cangkang Kemiri dan Natrium Karbonat Terhadap Sifat Mekanik dan Struktur Mikro pada Baja Mild Stell - Yushario Aqmal Kurniawan; Agung Supriyanto (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
contain other mixed materials. Mild steel has different grades determined by differences in carbon levels. This material has the characteristic of not being easily broken. Mild steel is also known as low-carbon steel. The purpose of this study is to identify the results of experiments on the chemical components of the bracket panel, identify the effect of immersion time on the hardness of the layer and the wear resistance of the bracket panel elements. In this study the author observed the impact of various masses in the carburizing stage on the thickness of the oxide surface and the hardness of the Mild steel layer with a furnace process with a temperature of 930ºC with a holding time of 4 hours. Based on the results of the study, it shows that in the chemical composition test, the chemical components of the main elements. Wear Test with the results of the value after conducting a Wear Test on mild steel material, the results of the wear test have an average wear value of 0.000189499 mm3/kg.m, on a 30% carbon specimen with a b0 (mm) value of 1.0782 then 40% carbon an average of 0.000086258, with a value of 0.8294, at 50% carbon has a bo value (mm) of 1.2958 at 60% carbon with a value of 0.9060 so that Specific Wear (Ws) (mm3/kg.m) occurs 0.000112433. Vickers Hardness Test This test is carried out by etching, desmuting (erosion) the carburizing process with the carburizing process and the Candlenut Shell Charcoal Composition experienced a 30% increase or 197.83 VHN, the carburizing process with the carburizing process and a 4-hour holding time experienced a 40% increase or 260.3 VHN, and the carburizing process with the carburizing process and a 4-hour holding time experienced a 50% increase or 250.8 VHN. In the carburizing process with the carburizing process and a 4-hour holding time experienced a 60% increase or 226.76 VHN. So the average surface hardness value between the carburizing process with a high percentage value in the 40% composition.